PHYSIOLOGICAL EFFECTS OF LAVENDER, ROSEMARY, AND SAGE ESSENTIAL OILS ON THE CARDIOVASCULAR AND RESPIRATORY SYSTEMS - Shirmatova Madinabonu Odiljon kizi (Web of Journals Publishing, 2025)
The study investigates the physiological effects of lavender (Lavandula angustifolia), rosemary (Rosmarinus officinalis), and sage (Salvia officinalis) essential oils on the cardiovascular and respiratory systems. Essential oils derived from these medicinal plants are known for their complex biochemical composition and regulatory influence on autonomic nervous system activity. Experimental observations demonstrated that controlled inhalation of the essential oils produced moderate hypotensive and bronchodilatory effects, as well as improvement in oxygen saturation and pulse stability. These findings suggest that lavender, rosemary, and sage essential oils may have potential supportive value in maintaining cardiovascular and respiratory homeostasis, as well as in the prevention of functional disorders associated with stress and hypoxia.
Keywords: Lavender essential oil, Rosemary essential oil, Sage essential oil, Cardiovascular system, Respiratory system, Physiological effects, Aromatherapy, Autonomic regulation, Hypoxia prevention.